Menstimulasi Literasi Budaya Dan Kewargaan Melalui Tembang Dolanan Jawa Di Ra Baitul Muttaqien Selomerto - Riski, Anggun; Sulis Idawati; Ariesta luciana hendrika; Sultiyah; Hidayatu Munawaroh (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
This study aims to analyze the stimulation of cultural literacy and citizenship through Javanese dolanan songs at RA Baitul Mutaqin. This research is a qualitative research and data collected using observation, interview and documentation techniques. Observations are used to obtain data on the implementation of cultural literacy and citizenship stimulation through Javanese dolanan songs. Interviews were used to find out the initial process of initiating the stimulation of cultural literacy and citizenship through the Javanese Dolanan song. While the documentation is used to find out the activities carried out to stimulate cultural literacy and citizenship through the Javanese song Dolanan. Based on the results of data analysis on the implementation of cultural literacy and citizenship stimulation through the Javanese Dolanan song at RA Baitul Mutaqin Selomerto, it started from a lack of children's knowledge regarding cultural literacy and citizenship through the Javanese Dolanan song. Therefore, it is necessary to stimulate cultural literacy and citizenship through the Javanese Dolanan song performed by an early childhood educator.